Pengaruh Motivasi dan Kompetensi terhadap Kepuasan Kerja serta Dampaknya pada Kinerja Pegawai di Sekolah Tinggi Ilmu Ekonomi Graha Karya Muara Bulian - Miptahul Choiri (CITRA EKONOMI, 2022)
This research raises concerns about the influence of motivation and competence on job satisfaction and its impact on performance. This study was conducted in the College of Economics of Graha Karya Muara Bulian. The purpose of this study 1). To know the overview of motivation, competence, job satisfaction and employee performance 2). To know the influence of the effect and the influence of no motivation andcompetence to work satisfaction 3). To know the effect of the performance and influence is not in the motivation and competence of the employees 4). To know the impact of work satisfaction on employee performance 5). To know the influence of meocultivation and competence on employee performance through job satisfaction. Methods in the study through surveys and dissemination of the questionnaire, the results of the Surver questionnaire is analyzed in a descriptive, qualitative and verial, by converting the ordinance data to intervals and using the Path analysis tool Assisted by SPSS 20 program The results of this research show that 1) motivation, competence, job satisfaction and performance of employees at STIE Graha Karya Muara Bulian are assessed good, 2) the effect of the influence directly and not directly to the job satisfaction , as competence has the influence directly and does not directly affect the work, 3) The influence of the effect directly and not directly to the employee's performance, while the competency has a influence directly and not directly to the employee's performance. 4) Work satisfaction has an impact on the performance of employees. 5) Influence of motivation and competence on employee performance through job satisfaction.